Effect of in-situ gas changes on thermally grown chromia scales formed on Ni–25Cr alloy at 1000°C in atmospheres with and without water vapour. (January 2015) - Simon, D.; Gorr, B.; Hänsel, M.; Shemet, V.; Christ, H.-J.; Quadakkers, W. J.
Abstract : Regarding oxidation resistance, most high temperature alloys rely on the formation of a protective chromia surface scale during service. In the present study, the oxidation behaviour of a Ni–25%Cr model alloy was investigated during single- and two-stage oxidation in Ar–O2 and Ar–H2 O gas mixtures at 1000°C. In the two-stage experiments, the test gas was changed after a predefined oxidation time from dry to wet gas, and vice versa, without intermediate specimen cooling. Oxidation kinetics were measured using thermogravimetry and post exposure characterisation was accomplished using scanning and transmission electron microscopy, focused ion beam and energy dispersive X-ray spectroscopy techniques. The single stage exposure to Ar–O2 resulted in the formation of a voided, poorly adhering chromia scale exhibiting a coarse, equi-axed morphology. In Ar–7%H2 O a fine, columnar grained oxide scale was formed which was free of microvoidage within the scale and at the scale/metal interface and therefore exhibited excellent adherence to the metallic substrate. During two-stage exposure to Ar–O2 and subsequently to Ar–H2 O, a fine grained, columnar shaped oxide developed on top of the coarse oxide scale formed in the first oxidation stage. The opposite effect occurred when the exposure started in the wet environment. The mechanisms which are responsible for the observed oxidation features are discussed on the basis of classical oxidation theory in combination with previous results on oxidation of chromia forming alloys in oxygen rich gases and water vapour containing, low p(O2 ) environments.